The role of primary care in preventing male suicide. (2nd November 2019) - Hardy, Sheila
Abstract : Men in the UK are three times more likely to take their own lives than women. Sheila Hardy describes how practice nurses can help to prevent these unnecessary deaths Men are more likely to die by suicide than women in the UK. Studies have found that most people whose death was due to suicide had been in contact with primary care in the year prior to death. Primary care clinicians, including practice nurses, are often the first health professionals seen by people who are experiencing distress or suicidal thoughts, and mental illness is mainly managed in primary care. However, mental illness is unrecognised in two-thirds of primary care patients. This article describes the responsibilities of health professionals in primary care consulting with men who may be at risk of suicide.